Synthesis and reactivity of [18F]-N-fluorobenzenesulfonimide - Teare, H; Robins, E; Årstad, E; Luthra, S; Gouverneur, V (2007)
A novel [18F]NF reagent and two novel radiochemical transformations have been developed: [18F]NFSi has been prepared from sodium dibenzenesulfonimide and reacted in the presence of silyl enol ethers and allylsilanes to deliver labelled fluorinated ketones and allylic fluorides respectively; the radiosynthesis of the fluorinated A ring of vitamin D 3 has also been completed with success. © The Royal Society of Chemistry.